First-Generation EGFR-TKI Plus Chemotherapy Versus EGFR-TKI Alone as First-Line Treatment in Advanced NSCLC With EGFR Activating Mutation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wu, Qiang; Luo, Wuxia; Li, Wen; Wang, Ting; Huang, Lin; Xu, Feng (Frontiers in Oncology, 2021)
Objective: The aim of this meta-analysis was to evaluate efficacy and toxicity of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) in combination with chemotherapy (CT) compared to EGFR-TKI monotherapy as first-line treatment in advanced non-small cell lung cancer (NSCLC) harboring activating EGFR mutation. Methods: A systematic literature search of randomized controlled trials using Cochrane Library, PubMed, Embase, and Web of Science, was performed up to Jan. 7th, 2020. Hazard ratios (HRs) with 95% confidence intervals (CI) were calculated as effect values for progress-free survival (PFS) and overall survival (OS). Risk ratio (RR) and Odds ratio (OR) were calculated as effect values for objective response rate (ORR) and toxicity, respectively. Results: A total of eight randomized trials involving 1,349 advanced NSCLC patients with sensitive EGFR mutation were included in the meta-analysis. All patients in both groups received first-generation TKI as first-line treatment. The pooled HR of PFS and OS was 0.56 (95% CI=0.50-0.64; P < 0.00001) and 0.70 (95% CI=0.54-0.90; P=0.005), respectively. Subgroup analysis showed significantly higher OS advantages in patients receiving doublet CT (P=0.02) and concurrent therapy (P=0.002). The ORR in the EGFR-TKI plus CT group was significantly higher than in the EGFR-TKI monotherapy group (RR = 1.18, 95% CI = 1.10–1.26). The combination regimen showed a higher incidence of chemotherapy-induced toxicities. Subgroup analysis indicated that doublet chemotherapy rather than single-agent chemotherapy significantly increased incidence of grade 3 or higher leukopenia, neutropenia and anemia. Conclusions: Compared with EGFR-TKI monotherapy, the combination of first-generation EGFR-TKI and CT, especially when applying concurrent delivery of platinum-based doublet chemotherapeutic drugs, significantly improve ORR and prolong PFS and OS in first-line treatment for advanced EGFR-mutated NSCLC. Although increasing incidence of chemotherapy-induced toxicities occurs in the combination group, it is well tolerated and clinically manageable.